Interleukin-8 as a prognostic serum marker in canine mammary gland neoplasias - Gelaleti, Gabriela Bottaro [UNESP]; Jardim, Bruna Victorasso [UNESP]; Leonel, Camila [UNESP]; Moschetta, Marina Gobbe; Pires de Campos Zuccari, Debora Ap [UNESP] (Elsevier B.V., 2012)
Mammary gland tumors in female dogs are an excellent model for the clinic-pathological, diagnostic and prognostic investigation of mammary neoplasias. Prognostic and predictive markers are effective in research and routine diagnosis. Interleukins play a fundamental role in cancer, with a particular function in tumor growth, invasion and metastatic potential. Interleukin-8 (IL-8) is known to possess tumorigenic and pro-angiogenic properties, and its overexpression is seen in a number of human tumors. IL-8 serum levels were determined and correlated with the clinic-pathological features and clinical evolution of mammary gland neoplasias in female dogs. IL-8 was measured by an immunoenzymatic assay in 30 female dogs with mammary neoplasias within a 12 month follow-up and in 50 control animals. The correlation between IL-8 concentration and clinical parameters was investigated. A statistically significant difference in the IL-8 serum levels was found in tumor-bearing dogs compared to the controls. In addition, when the individual parameters were evaluated, IL-8 content showed a positive correlation with the tumor progression, lymph node involvement, recurrence and death. Single and multivariate analyses showed associations between tumor recurrence, metastasis, high clinical staging and high IL-8, and also with the death risk. This was also consistent with the high IL-8 content in dogs showing tumor recurrence and metastasis. IL-8 superexpression has been detected in a number of human tumors, usually associated with a poor prognostic. Besides promoting angiogenesis, IL-8 is strongly related with the metastatic phenotype of mammary tumor cells. High IL-8 concentration was found in mammary gland cancer patients with advanced disease stages. Our results show that IL-8 can be used as a non-invasive prognostic marker for mammary gland cancer, and can be useful for the prediction of disease progression and recurrence in dogs with mammary neoplasias. The increased level of this cytokine acts as an independent prognostic marker of survival and the identification of animals with the poor prognostic. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Interleukin-8; Mammary neoplasia; Prognostic factors